Social Change and the Changing Indian Voter: Consolidation of the BJP in India's 2019 Lok Sabha Election. (December 2019) - Suri, K. C.
This article is about the changing voter in a changing India in the context of India's Lok Sabha election held in the year 2019. Positing a two-way relationship between social change and electoral politics, this article analyses the sources for the success of the Bharatiya Janata Party (BJP) in mobilizing massive support among various Hindu social groups. It examines the claims of the BJP leaders that the 2019 election has breached the barriers of caste and class. It takes the view that the social change over the decades after independence, especially after the 1990s, led to the emergence of a new elite composed of members from different social groups with shared values and social life willing to join hands for political purposes and that led to the massive victory of the BJP in the absence of any other viable alternative.